2011
DOI: 10.1177/1941875210383176
|View full text |Cite
|
Sign up to set email alerts
|

Status Epilepticus

Edward M. Manno

Abstract: Status epilepticus is a neurological emergency that is commonly encountered by the neurohospitalist. Successful treatment depends upon the recognition of prolonged seizure activity and the acute mobilization of available resources. Pharmacologic treatment regimens have been shown to decrease the time needed for successful control of seizures and have provided for the rapid administration of anticonvulsant medications. Treatment strategies have evolved so that clinicians can administer effective doses of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The definition of SE has been constantly changing. It is also suggested that it depends on the context of SE, in humans or experimental models ( 11 , 12 ). There has been a consensus that the duration or length of convulsive seizures (CS) during SE should be sufficient to cause long-term brain injury, enabling the brain to generate spontaneous seizures i.e., “an enduring epilepticus” ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of SE has been constantly changing. It is also suggested that it depends on the context of SE, in humans or experimental models ( 11 , 12 ). There has been a consensus that the duration or length of convulsive seizures (CS) during SE should be sufficient to cause long-term brain injury, enabling the brain to generate spontaneous seizures i.e., “an enduring epilepticus” ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seizures are normally self-terminated by activating inhibitory mechanisms. Failure of these mechanisms can result in prolonged seizures (SE), which may require interventional drugs ( 12 ). However, according to the clinical trial guidelines, the treatment should be initiated only if the CS last for ~5 min ( 11 , 14 – 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment of SE in patients and animals is focused on the prompt delivery of benzodiazepines such as diazepam or midazolam [7]. Additionally, in animal models of SE induced by chemoconvulsants, organophosphate toxicity, or nerve agent exposure, anticholinergics such as scopolamine or atropine are often employed [8].…”
Section: Introductionmentioning
confidence: 99%
“…The duration and severity of SE determines the outcome of epileptogenesis. The definition of SE depends on the context, and has been constantly changing (Manno, 2011; Seinfeld, 2016). According to the recommendation of the Commission on Classification and Terminology and the Commission on Epidemiology of the International League Against Epilepsy (ILAE), the SE is defined as “ a condition resulting either from the failure of the mechanisms responsible for seizure termination or from the initiation of mechanisms, which lead to abnormally, prolonged seizures (after time point t1).…”
Section: Severity Of Status Epilepticus Determines Epileptogenesismentioning
confidence: 99%
“…This duration is now widely accepted for studies that investigate the long-term consequences of SE i.e., epileptogenesis and epilepsy (Commission on Epidemiology and Prognosis, 1993; Dodson et al, 1993). Seizures normally self-terminate by activating the inhibitory mechanism, however, if this mechanism fails it can lead to prolonged seizures (SE), which may then require administration of intervention drugs to terminate SE (Manno, 2011). Interestingly, the clinical trial guidelines recommend ~5 min to intervene in the case of continuous convulsive seizures (Dodson et al, 1993; Lowenstein et al, 1999; Shinnar et al, 2001; Seinfeld et al, 2016).…”
Section: Severity Of Status Epilepticus Determines Epileptogenesismentioning
confidence: 99%